2014
DOI: 10.4103/1319-2442.124501
|View full text |Cite
|
Sign up to set email alerts
|

Renovascular hypertension: A report of 21 cases

Abstract: Renovascular hypertension (RVH) is among the most common forms of secondary hypertension. We studied 21 patients (eight male and 13 female) with RVH who were encountered during a period of 16 years. The average age of the patients was 34.75 years. Trans-renal Doppler ultrasound confirmed the diagnosis of renovascular stenosis (RAS) as the cause of RVH in 95% of the patients. Computed tomography angiography was performed in ten cases, which confirmed the diagnosis in all these cases. Magnetic resonance angiogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
0
3
0
2
Order By: Relevance
“…Consequentemente à esta hipoperfusão,ocorrem ativação de vias inflamatórias nos rins, levando a estresse oxidativo e disfunção endotelial que podem culminar em nefropatia isquêmica e fibrose intersticial do parênquima renal. 4,5 São causas conhecidas de HSEC renovascular: aterosclerose de artéria renal, displasia fibromuscular, arterite de takayasu. Estas seriam as causas mais descritas, sendo o diagnóstico de aterosclerose percentualmente mais diagnosticado.…”
Section: Discussionunclassified
“…Consequentemente à esta hipoperfusão,ocorrem ativação de vias inflamatórias nos rins, levando a estresse oxidativo e disfunção endotelial que podem culminar em nefropatia isquêmica e fibrose intersticial do parênquima renal. 4,5 São causas conhecidas de HSEC renovascular: aterosclerose de artéria renal, displasia fibromuscular, arterite de takayasu. Estas seriam as causas mais descritas, sendo o diagnóstico de aterosclerose percentualmente mais diagnosticado.…”
Section: Discussionunclassified
“…Hipertensi renovaskular adalah peningkatan tekanan darah sistolik dan atau diastolik yang umumnya mendadak dan resisten akibat hipoperfusi ginjal yang biasanya disebabkan stenosis arteri renalis dan aktivasi sistem renin-angiotensin. 1 Hipertensi renovakular dapat terjadi karena gangguan pada vaskular, berkaitan dengan penyakit parenkim ginjal atau dapat juga merupakan kombinasi dari keduanya. Hipertensi renovaskular merupakan 1-4 % dari seluruh penderita hipertensi.…”
Section: Pendahuluanunclassified
“…In 2K1C model, partial occlusion of the renal artery (stenosis) leads to reduced blood flow and perfusion pressure, causing renovascular hypertension (RVH), a disease regarded as a secondary hypertension form in humans [ 14 ]. Renal artery stenosis activates the renin–angiotensin–aldosterone system (RAAS), promoting oxidative stress, inflammation, microvascular loss, severe interstitial fibrosis and tubular atrophy, resulting in functional kidney deterioration [ 12 , 13 ] and further progress to CKD and renal failure [ 15 ]. We have recently shown that MSC renal subcapsular administration led to a significant reduction in blood pressure arguing a strong effect on renin release by actions on juxtaglomerular apparatus.…”
mentioning
confidence: 99%